Insight into the energy level structure and luminescence process of color centers at SiO2/SiC interfaces - Kentaro Onishi; Takato Nakanuma; Haruko Toyama; Kosuke Tahara; Katsuhiro Kutsuki; Heiji Watanabe; Takuma Kobayashi (APL Materials)
We investigated the correlation between electrically active defects and color centers at the SiO2/SiC interface, aiming to clarify the electronic and optical properties of the color centers. SiO2/SiC samples were formed by varying the oxidation temperature and oxygen partial pressure within 1400–1600 °C and 0.05%–100%, respectively. The results showed that the integrated photoluminescence intensity of the color centers is strongly correlated with the effective fixed charge density obtained from the flatband voltage shift in the capacitance–voltage characteristics. The effective fixed charges mainly originate from an acceptor level located at energies within (EC − 0.65)–(EC − 0.92) eV, which was estimated from the plateau capacitance of each sample. Therefore, the origin of color centers lies in a deep acceptor-type defect. Based on the results obtained, we discussed the possible luminescence process and the origin of color centers. Referring to previous theoretical calculations, we consider dicarbon antisite [(C2)Si] in near-interface SiC as a main candidate of the color centers found at the SiO2/SiC interface.